PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI DI FAKULTAS EKONOMI UNIVERSITAS JEMBER - Hasan, Farida; Sularso, Andi; Handriyono, Handriyono (Relasi : Jurnal Ekonomi, 2016)
Based on the results of research in the Faculty of Economics, University of Jember on the influence of the physical work environment, organizational culture and work motivation on employee performance This study used path analysis (Path Analysis) with data processing using Statistical Product and Service (SPSS Versi.15) The results of the study show that the Physical Working Environment (X1), and Cultural Organization (X2), the motivation of Work (Y1) simultaneously positive and significant effect on employee performance (Y2). This can be concluded when the fourth variable is certainly increased employee performance also increased. Physical Work Environment (X1) partially not significant effect on employee performance (Y2). But with the results of a positive coefficient of the working environment then lambatlaun improve the performance of the company to generate better employment process takes long enough to be supported by a conducive environment, the results of the work will be the maximum in accordance with the desired company. Cultural Organization (X2) partially not significant effect on employee performance (Y2). Good organizational culture will produce output that is also good that the realignment of work habits do not tutas should be avoided. Motivation (Y1) partially positive and significant impact on employee performance (Y2). Motivation needs to be improved in an effort to stimulate the performance of employees, with rewards for the work that deserved the employee will improve its performance which will have a positive impact on the company.